Propuesta de creación de una oficina de auditoria interna en la Empresa Bermanlab, para mejorar la eficiencia operativa, en el distrito de Trujillo, año 2015. - Ramos Hoyos, Lucky Lukhiano (2016)
This research entitled "Proposal for the establishment of an office of internal audit in the company Bermanlab, to improve operational efficiency, in the district of Trujillo, 2015", was held due to the occurrence of problem situations continuously in BERMANLAB company, by the fact that they don’t have an internal audit department that is responsible for evaluating processes and integrate areas as their areas work separately. As mentioned above, this Research had like main objective is to demonstrate that the proposed creation of an office of internal audit through the procedures used and the current regulations, improve operational efficiency in Bermanlab. The research was conducted according to an investigation of applicative type, since the data for this research will be obtained from the company, which will be studied and analyzed in order to determine the acceptance of the proposal to create an office of internal audit in BERMANLAB. Through the application of a survey based on the components of internal control, it could analyze the current situation of the company operationally, to meet management control, identify risks, control environment, information system and supervision. In addition a risk map that allowed us to demonstrate that the application of preventive measures reduces the risk and improves operational efficiency was used. Presenting some operational solutions addressing the identified deficiencies in the company, which will be addressed through an internal audit, using the COSO model. The conclusion reached with this research is that the proposed creation of an Office of Internal Audit will significantly improve the operational efficiency of the Company Bermanlab according to the guidelines of the COSO model. In the investigations and techniques used highlights that despite having Internal Control procedures, you need them to be improved and updated to provide support to senior management with greater control in all areas, for meeting institutional goals, showing that the proposed creation of an Office of Internal Audit should be accompanied by changes in organizational culture.